Original paperEstimating the subjective efficiency after treatment of upper extremity hyperhidrosis using various methods - Wachal, Krzysztof; Bućko, Wojciech; Staniszewski, Ryszard; Majewska, Natalia; Błaszak, Magda (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Introduction: There are many alternative methods used in treating hyperhidrosis. Unfortunately, none of them is one hundred per cent effective. All of them have some defects as well as advantages. Material and methods: In our research we observed 43 patients treated using various methods. We used iontophoresis in the first group, and in the second we applied botulinum toxin injections. In group three we applied a surgical procedure: endoscopic thoracic sympathectomy. After using those various methods patients’ subjective feelings were compared. Results and conclusions: In our research we found that surgical treatment of spontaneous hyperhidrosis gives the best subjective results; the effect lasted the longest in comparison with botulinum toxin injections and iontophoresis. Simultaneously we observed that not all of the patients could accept the difficulties and the possibility of complications after surgical operation. In such cases we suggest the use of botulinum toxin injections at regular 6-month intervals or iontophoresis repeated a few times.